2022
DOI: 10.1002/lary.30351
|View full text |Cite
|
Sign up to set email alerts
|

Novel Machine Learning Model to Predict Interval of Oral Cancer Recurrence for Surveillance Stratification

Abstract: Objective(s) We aimed to develop a machine learning (ML) model to accurately predict the timing of oral squamous cell carcinoma (OSCC) recurrence across four 1‐year intervals. Methods Patients with surgically treated OSCC between 2012–2018 were retrospectively identified from the Yale‐New Haven Health system tumor registry. Patients with known recurrence or minimum follow‐up of 24 months from surgery were included. Patients were classified into one of five levels: four 1‐year intervals and one level for no rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Among these, three studies also evaluated traditional linear models, with the AUROC for corresponding ML models ranging from 0.67 to 0.88, while for linear models including logistic regression, it ranged from 0.68 to 0.73 [ 64 , 79 , 84 ]. Additionally, six studies provided F-1 scores for ML models, with values ranging from 0.53 to 0.89 [ 57 , 59 , 62 , 69 , 79 , 84 ]. Of these, three studies included F1-scores for linear models as well, with the corresponding ML models’ F1-scores ranging from 0.53 to 0.89 and linear models’ scores from 0.30 to 0.87 [ 69 , 79 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, three studies also evaluated traditional linear models, with the AUROC for corresponding ML models ranging from 0.67 to 0.88, while for linear models including logistic regression, it ranged from 0.68 to 0.73 [ 64 , 79 , 84 ]. Additionally, six studies provided F-1 scores for ML models, with values ranging from 0.53 to 0.89 [ 57 , 59 , 62 , 69 , 79 , 84 ]. Of these, three studies included F1-scores for linear models as well, with the corresponding ML models’ F1-scores ranging from 0.53 to 0.89 and linear models’ scores from 0.30 to 0.87 [ 69 , 79 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, six studies provided F-1 scores for ML models, with values ranging from 0.53 to 0.89 [ 57 , 59 , 62 , 69 , 79 , 84 ]. Of these, three studies included F1-scores for linear models as well, with the corresponding ML models’ F1-scores ranging from 0.53 to 0.89 and linear models’ scores from 0.30 to 0.87 [ 69 , 79 , 84 ]. Besides the oral cavity, other sites either had no or only one related study, so their results could not be consolidated.…”
Section: Resultsmentioning
confidence: 99%
“…The research on establishing a machine learning model to predict the recurrence time of oral squamous cell carcinoma not only verified the view that postoperative recurrence of oral cancer is mainly concentrated in the first 2 years after surgery but also confirmed that the predictive performance of the AI machine learning model is better than that of other models; the results supported the view that the prediction of characteristic variables is more accurate. 36 Using individual characteristic variables to establish a prediction model can make each case more characteristic, but screening more factors related to postoperative recurrence for comprehensive variable prediction is expected to provide more comprehensive prediction results.…”
Section: Discussionmentioning
confidence: 99%